Genetically Modified Food: What Are Mainers Thinking? - Teisl, Mario; Garner, Luke; Roe, Brian; Vayda, Michael (Maine Policy Review, 2004)
Whether to allow genetically modified (GM) foods in Maine, and if so, under what circumstances, has been hotly debated in recent years. The authors explore one aspect of the issue—Mainers’ attitudes about the labeling of GM foods. They point out that labeling GM foods is more complex than simply whether to label. Policy decisions need to be made about whether labeling should be mandatory, what pieces of information should be on the label, who should be in charge of monitoring compliance, and even what foods should be labeled. The authors discuss the potential benefits of GM food labeling, and conclude that simply labeling foods as “genetically modified” would be of relatively little use since there would not be enough information for consumers to make informed decisions about what they buy.
Keywords: Maine; genetically modified food